Technical Progress, Factor Productivity and Macroeconomic Performance in the Medium Term - Giorno, Claude (OECD Economics Department Working Papers, 1995)
This paper examines the possible short- and medium-term macroeconomic consequences of changes in trend factor productivity growth for the major OECD economies. The analysis includes a range of different scenarios based on the recently re-estimated OECD INTERLINK model, in particular its supply-side properties, which illustrate a range of uncertainties and the sensitivity of the adjustment mechanisms to macroeconomic and structural factors. Overall the results suggest that a rise in trend factor productivity will lead to higher levels of production and real income, but employment adjustment will depend on the extent to which the long-run equilibrium of an economy is affected. Though unemployment could rise temporarily, there are important mechanisms present which, if functioning correctly, should prevent any permanent increase in unemployment. The degree of market flexibility is, however, seen as being crucial to the adjustment process, with higher rigidities tending to lengthen the ...